If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2u = 3 Solving 7 + 2u = 3 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2u = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 2u = 3 + -7 2u = 3 + -7 Combine like terms: 3 + -7 = -4 2u = -4 Divide each side by '2'. u = -2 Simplifying u = -2
| 18=-6y+4(y+6) | | -(-2)-1=1 | | -41=-7x+3x+7 | | X^2+4c-32=0 | | n+0.6n=64 | | 3(2x)=6x-7 | | 3(2)=6x-7 | | -16=23 | | r=4K-9S | | 4x^2+33x-8=0 | | n+5=-9 | | 12r+8=32 | | 14=2l+4w-1 | | 3*24-9+8x+12=180 | | X-8-7x-9-2x=38 | | 90=x+x+4+3x-9 | | 2x+3(1)=11 | | 4(u+6)-7u=3 | | 3x+(3x+6)=5 | | 3(4)+5y=17 | | 15t-5t^2+3t^32=0 | | 3n^2-6n+7=0 | | 3(x+4)+2x-6+5(-x-1)= | | Y=1(x-5)+3 | | 14=2L+4W | | (3a^2)-6x-9= | | 3a+6+5a-2a=2 | | 4(w-2.1)=.6 | | 9x^8-4x^7-5x-18=0 | | 4y=165 | | 3(x-2)+7=4(2+x) | | 9+m=15 |